Mobile-Based Augmented Reality Application in Pharmacy Schools Implemented in Pharmaceutical Compounding Laboratories: Students' Benefits and Reception - Mohamed Ismail Nounou; Heba A. Eassa; Kamila Orzechowski; Hadeer A. Eassa; Jerry Edouard; Nicole Stepak; Mohammad Khdeer; Mohammed Kalam; Diana Huynh; Eric Kwarteng; Kamilia H. A. Mohamed; Nada A. Helal; et al. (MDPI AG, 2022)
Background: Augmented reality (AR) is a technological approach which combines virtual objects such as text, pictures or videos with physical objects (real-world). The study aimed to design, implement and validate a mobile-based AR application, as a self-paced, interactive, student-centered learning tool be used in the pharmaceutical compounding laboratory course for first year pharmacy students. Method: A mobile-based AR application (Amplified Rx app; HeyPayLess Inc) compatible with iOS and android operating system was developed. A cross-over study design was conducted where alternatively, one group was subjected to ARx app implementation in 8 formulations and the other group served as control. The reception and benefits to students were assessed via a 10 questions survey. In this case, 69 (2019) and 55 (2020) students participated in the study. Result: Students' use of ARx app was increased in 2020 which indicates its usefulness. For acceptability, leaners enjoyed interactive materials and tutorial videos were the most used and appealing item. Learners described the installation, scanning and operation to be very easy in both years. 86.95% of learners were confident conducting the experiments with the assistance of ARx app in 2019 and increased to 92.73% in 2020. 33.33% considered ARx app to be the most helpful resource in 2019, and the percent was significantly increased to 76.36% in 2020. Conclusion: AR technology implementation in pharmaceutical education could create student-centered engaging and interactive learning experience in fundamental areas such as pharmaceutical compounding laboratories.